# Solve for y 2z(4y+9)-3y=11

2z(4y+9)-3y=11
Simplify each term.
Apply the distributive property.
2z(4y)+2z⋅9-3y=11
Rewrite using the commutative property of multiplication.
2⋅4(zy)+2z⋅9-3y=11
Multiply 9 by 2.
2⋅4(zy)+18z-3y=11
Multiply 2 by 4.
8zy+18z-3y=11
8zy+18z-3y=11
Subtract 18z from both sides of the equation.
8zy-3y=11-18z
Factor y out of 8zy-3y.
Factor y out of 8zy.
y(8z)-3y=11-18z
Factor y out of -3y.
y(8z)+y⋅-3=11-18z
Factor y out of y(8z)+y⋅-3.
y(8z-3)=11-18z
y(8z-3)=11-18z
Divide each term by 8z-3 and simplify.
Divide each term in y(8z-3)=11-18z by 8z-3.
y(8z-3)8z-3=118z-3+-18z8z-3
Cancel the common factor of 8z-3.
Cancel the common factor.
y(8z-3)8z-3=118z-3+-18z8z-3
Divide y by 1.
y=118z-3+-18z8z-3
y=118z-3+-18z8z-3
Simplify 118z-3+-18z8z-3.
Move the negative in front of the fraction.
y=118z-3-18z8z-3
Combine the numerators over the common denominator.
y=11-18z8z-3
y=11-18z8z-3
y=11-18z8z-3
Solve for y 2z(4y+9)-3y=11

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top